American Tegumentary Leishmaniasis in Montes Claros: an epidemiological study (Research, Society and Development, 2021)
Introduction: American Tegumentary Leishmaniasis (ATL), or kala azar, is a serious chronic disease caused by Leishmania spp. It is an infectious and non-contagious disease that affects both humans and several species of wild and domestic animals, presenting the clinical forms of cutaneous, mucocutaneous and diffuse cutaneous. ATL is classified as a generalized zoonotic disease that has a global impact. It is caused by protozoa of the genus Leishmania and is considered a serious public health problem. Objective: To describe the epidemiological profile of cases found in Montes Claros-MG. Methodology: An epidemiological assessment was performed based on secondary data from SINAN/MS from January 2010 to December 2015. Results: From 2010 to 2015, 286 cases of ATL were registered, with the majority of cases occurring in children under 19 years of age (31.81%) and patients over 59 years (17.83%) had a lower percentage of disease involvement. The first choice drug used by patients was Glucantime (87.06%). The most affected gender was male (52.44%) and most patients had no comorbidities (76.96%). Conclusion: In Montes Claros, Minas Gerais, ATL presented high cases during the research period. In this sense, this study guides the development of new researches that address and monitor the spread of the disease by monitoring urban areas concomitantly with the capture of animals for the presence of the parasite, thus assisting in public health decision-making in controlling the disease.